A topographically preserved road‐network tile model and optimal routing method for virtual globes. Issue 2 (13th January 2019) - Dong, Quanhua; Chen, Jing; Liu, Tingting
Abstract: Virtual globes enable the combination of heterogeneous datasets for optimal routing analyses in transportation, environmental ecology, and construction engineering. In this study, considering the advantages of the hierarchical tiling structure and topography of virtual globes, we propose a tile‐based optimal routing method for large‐scale road networks in a virtual globe. This method designs a topographically preserved road‐network tile model by partitioning roads into tiles and constructs the road‐network pyramid from the bottom to the top. During construction, a TileArc is calculated and flagged as the shortest path in a tile. Based on the built road‐network pyramid carrying hierarchical TileArcs, a multi‐level and flexible shortest path query can be executed efficiently. The proposed method is implemented with large road networks with different road grades in a virtual globe. Experimental results verify its validity, efficiency, and exactness. Moreover, the length of the shortest path with surface distance is approximately 1.3 times longer than that with Euclidean distance.